Monopsonistic Labor Markets and International Trade - Priyaranjan Jha; Antonio Rodriguez-Lopez (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper introduces a framework to study the impact of trade liberalization on wage inequality and welfare in the presence of monopsonistic labor markets. The interaction of firm heterogeneity in productivity with idiosyncratic preferences of workers for working at different firms generates between-firm wage inequality for workers with identical skills. The degree of monopsony power is captured by the elasticity of firm-level labor supply, with a lower elasticity implying more wage-setting power by the firm. With more productive firms paying higher wages, monopsony power dampens the impact of firm heterogeneity on the allocation of market shares and allows lower productivity firms to survive. In a closed economy this increases inequality, but in an open economy high levels of monopsony power inhibit exporting, which may reduce inequality by compressing wages on the right side of the distribution. Nevertheless, inequality in the open economy is always higher than in autarky. Monopsony power reduces social welfare (for empirically plausible values of the labor supply elasticity) and the gains from trade.
Keywords: F12; F13; F16; 330; monopsonistic labor market; wage inequality; trade liberalization